University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 7 - Section 7.3 - Hyperbolic Functions - Exercises - Page 417: 9



Work Step by Step

We apply hyperbolic function formulas: $ \cosh x= \dfrac{e^x+e^{-x}}{2}$ and $ \sinh x= \dfrac{e^x-e^{-x}}{2}$ Thus, $(\sinh x + \cosh x)^4=[\dfrac{e^x-e^{-x}}{2}+\dfrac{e^x+e^{-x}}{2}]^4=[\dfrac{2e^x}{2}]^4=e^{4x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.